FACTORS THAT AFFECT THE PERFORMANCE OF HONORARY HEALTH WORKERS AT THE UPT PUSKESMAS LOTU REGENCY NORTH NIAS - Zega, Perdamaian; Theo, Deli; Effendy, Ismail (HEARTY, 2025)
Health workers play an important role in improving the quality of services at health centers through direct interaction with patients. However, the performance assessment of honorary health workers at the Lotu Health Center Unit showed an achievement of only 47%, so an analysis of the factors that affect it was needed. This study used a quantitative design with a cross sectional approach on 34 honorary nurses with a total sampling technique. The analysis was carried out univariately, bivariately, and multivariate using logistic regression tests. The results showed that workload (p=0.015), work stress (p=0.008), work environment (p=0.001), incentives (p=0.003), and compensation (p=0.000) had an effect on the performance of honorary health workers. It was concluded that these factors need to be considered by management to improve the performance of health workers and the quality of services at the health center.